Synthesis of thienyl analogues of PCBM and investigation of morphology of mixtures in P3HT - Matsumoto, Fukashi; Moriwaki, Kazuyuki; Takao, Yuko; Ohno, Toshinobu (Beilstein Journal of Organic Chemistry, 2008)
Novel [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) analogues containing benzo[b]thiophene (3a, 3b) and thieno[3,2-b]thiophene (3c, 3d) were synthesized and characterized. The morphology of the thin films prepared from the mixtures of these methanofullerenes with regioregular poly(3-hexylthiophene) (P3HT) was investigated by AFM measurement and UV-Vis absorption spectroscopy. A solubility test of these methanofullerenes was performed by using dichloromethane as a solvent. es-TThCBM (3d) exhibited 1.4 times greater solubility in dichloromethane than PCBM.
Keywords: fullerene; morphology; organic fullerenes; PCBM; photovoltaic cell